Antidepressant Treatment Duration in Pediatric Depressive and Anxiety Disorders: How Long is Long Enough? - Hathaway, Elizabeth E. (Curr Probl Pediatr Adolesc Health Care, 2018)
Anxiety and depressive disorders are common in the pediatric primary care setting, and respond to both psychotherapeutic and antidepressant pharmacotherapy treatment. However, there are limited data regarding the optimal treatment duration. This paper systematically reviews guidelines and clinical trial data related to antidepressant treatment duration in pediatric depressive and anxiety disorders. The extant literature suggests 9–12 months of SSRI treatment for youth with major depressive disorder. For generalized, separation and social anxiety disorders, 6–9 months of SSRI treatment may be sufficient, though many clinicians extend treatment to 12 months based on extrapolation of data from adults with anxiety disorders. Such extended treatment periods may decrease the risk of long-term morbidity and recurrence; however, the goal of treatment is ultimately remission, rather than duration of antidepressant pharmacotherapy. Evidence-based guidelines represent a starting point; however, appropriate treatment duration varies and patient-specific response, psychological factors, and timing of discontinuation must be considered for individual pediatric patients.